2016
DOI: 10.1155/2016/5057610
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Developing Rat Brain due to Production of Reactive Oxygen and Nitrogen Species

Abstract: Oxidative stress after birth led us to localize reactive oxygen and nitrogen species (RONS) production in the developing rat brain. Brains were assessed a day prenatally and on postnatal days 1, 2, 4, 8, 14, 30, and 60. Oxidation of dihydroethidium detected superoxide; 6-carboxy-2′,7′-dichlorodihydrofluorescein diacetate revealed hydrogen peroxide; immunohistochemical proof of nitrotyrosine and carboxyethyllysine detected peroxynitrite formation and lipid peroxidation, respectively. Blue autofluorescence detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Supporting these findings, previous observations, obtained on the same animal model, showed both early and persistent increased levels of 8-hydroxydeoxyguanosine (8OHdG), an indirect marker of oxidative stress, and NOX2, a ROS-producing enzyme, in the same brain region ( Schiavone et al, 2020 ). Accordingly, it has been reported that, although oxidative stress contributes to the physiological postnatal brain development in rodents, the effects of increased ROS levels on the CNS, following an external insult, might be revealed later in life ( Wilhelm et al, 2016 ). Moreover, antioxidant treatment with N-acetyl cysteine in mice could prevent cognitive and behavioral dysfunctions at adulthood, resulting from ketamine administration at PNDs 7, 9, and 11 ( Phensy et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these findings, previous observations, obtained on the same animal model, showed both early and persistent increased levels of 8-hydroxydeoxyguanosine (8OHdG), an indirect marker of oxidative stress, and NOX2, a ROS-producing enzyme, in the same brain region ( Schiavone et al, 2020 ). Accordingly, it has been reported that, although oxidative stress contributes to the physiological postnatal brain development in rodents, the effects of increased ROS levels on the CNS, following an external insult, might be revealed later in life ( Wilhelm et al, 2016 ). Moreover, antioxidant treatment with N-acetyl cysteine in mice could prevent cognitive and behavioral dysfunctions at adulthood, resulting from ketamine administration at PNDs 7, 9, and 11 ( Phensy et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable increase of reactive oxygen species (ROS) is one of the pathophysiological characteristics of diabetes [40]. ROS can not only directly cause oxidative damage of tissues and organs but also indirectly inhibit the activity of the endothelial nitric oxide synthase (eNOS) via the decoupling and activation of PKC- β , which induces the production of peroxynitrite anion (ONOO − ) with stronger protein nitration ability and cytotoxicity, thereby aggravating the injury [41, 42]. It suggests that the enhancements of oxidative stress and the secondary damage caused by enhanced oxidative stress in diabetic state are probably the main reasons why the organs of diabetic patients are vulnerable to I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the possibility that local oxidative stress and inflammation events are indeed the key focal determinants of lesion development and may act in concert to drive CCM pathogenesis can explain the clear discrepancy between the pan-endothelial loss of CCM proteins and the focal nature of CCM lesions in neonatal mouse models (Boulday et al, 2011, Chan et al, 2011). Intriguingly, there is evidence that oxidative stress occurs after normal birth (Wilhelm et al, 2016), as well as that the immature brain is particularly susceptible to free radical injury because of its poorly developed scavenging systems and high availability of iron for the catalytic formation of free radicals (Blomgren and Hagberg, 2006). Besides providing further support to the role of oxidative stress in CCM pathogenesis, these observations could also explain why the formation of CCM-like lesions in neonatal mouse models of CCM disease occur only if the endothelial-specific deletion of CCM genes is induced immediately after birth (P1) but not in the adult phase (Boulday et al, 2011).…”
Section: Discussionmentioning
confidence: 99%